Pengaruh Kesadaran Agama, Kesadaran Sosial, dan Kemudahan Pembayaran Terhadap Tingkat Partisipasi Masyarakat Membayar Zakat Infaq Sedekah di Baznas Kabupaten Ponorogo - Karina Sukma Handayani Putri; Ahmad Kudhori; Yopie Diondy Kurniawan (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
This study aims to analyze the influence of religious awareness, social awareness, and payment convenience on the level of public participation in paying zakat, infaq, and sadaqah (ZIS) at BAZNAS in Ponorogo Regency. The research method employed is quantitative, with data collection through questionnaires. Data analysis was performed using multiple linear regression. The results indicate that religious awareness negatively affects the level of public participation in ZIS payment. Meanwhile, social awareness and payment convenience have a positive influence on this participation level. These findings suggest that increasing social awareness and providing easier payment systems can encourage public participation in paying ZIS, while the factor of religious awareness requires further study regarding its negative influence. This research contributes to BAZNAS in Ponorogo Regency in formulating strategies to increase public participation in ZIS payment.